Improving the techno-functionality of wild almond protein isolate-based films by its hydrolysates and cold plasma treatment - Zahra Tahsiri; Sara Hedayati; Mehrdad Niakousari (Food Hydrocolloids for Health)
In the present study, composite films (COFI) using wild almond protein isolate (WAPI) and Persian gum (PG) in a ratio of 9:1 and varying amounts (0, 0.15%, 0.30%, and 0.60% (W/V)) of wild almond protein hydrolysate (PH) were developed. The COFI was exposed to atmospheric cold plasma (CP). The physicochemical, antioxidant, and antimicrobial characteristics of COFI before and after CP exposure were evaluated. The inclusion of PH did not significantly influence the COFI's moisture content biodegradability; however, the film thickness and film water vapor permeability increased. As the amount of PH in the COFI rose from 0 to 0.60%, the total phenolic content as well as antioxidant activity (determined by the DPPH and ABTS assays) were enhanced. While not being effective against Escherichia coli, the COFI containing PH exhibited inhibitory effects against Staphylococcus aureus. CP treatment improved the COFI in terms of their mechanical attributes without compromising antimicrobial and antioxidant features. Analysis of the FTIR spectra showed detectable enhancements in peak intensity at 1400, 1538, and 1628 cm−1, while micrograph patterns displayed an increase in the coarseness of COFIs, following cold plasma treatment. Overall, the COFIs with 0.60% PH (W/V) treated with cold plasma were the most functionally favorable.